Digitalisasi, Literasi Keamanan Digital, dan Penguatan Branding Produk dalam Peningkatan Daya Saing UMKM di Kelurahan Srengsem, Bandar Lampung - Muhammad Hafizh Abdul Chalid; Nico Rafly renaldo (FT Universitas Lampung, 2026)
The utilization of digital technology has become essential for micro and small enterprises to enhance business competitiveness. However, many business actors in Srengsem Village still operate conventionally and have limited understanding of digital transaction security, making them vulnerable to online fraud. This community service program aims to improve the use of digital media for marketing, strengthen product identity through branding and packaging, and increase digital security literacy among business actors. Activities were conducted through business mapping, field visits, digital literacy education, assistance in managing social media accounts, and product packaging design development. Results indicate improved digital media utilization, stronger business identity through banners and product labels, and increased awareness of online fraud risks. The program also opens opportunities for continued assistance to support sustainable business development.